Corrosion-resistant film, pipe and preparation method and application thereof
Patent Information
- Application Number
- CN202510466746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-04-15
AI Technical Summary
然而,当金属管材处于苛刻环境时,十分容易被化学介质腐蚀导致管材变薄甚至破损,进而造成严重的经济损失,如当金属管材用于原油输送时,由于原油中含有硫化物、酸性物质、溶解性气体等具有腐蚀性的化学物质,进而会对管道内部进行腐蚀
[0046]1.本发明提供的耐腐蚀薄膜耐腐蚀性能和与金属的附着性能优秀,在苛刻环境中能够有效保护金属管材不易被腐蚀,不易脱落,有效延长管材寿命;
Smart Images

Figure BDA0005358700880000021 
Figure BDA0005358700880000091 
Figure BDA0005358700880000092
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials science, and in particular to a corrosion-resistant thin film, a pipe, its preparation method, and its application. Background Technology
[0002] Metal pipes are widely used in various industrial fields, such as the oil and gas industry, aerospace industry, shipbuilding industry, and power industry, due to their high strength and good performance. However, when metal pipes are in harsh environments, they are easily corroded by chemical media, causing the pipes to thin or even break, resulting in serious economic losses. For example, when metal pipes are used for crude oil transportation, the crude oil contains corrosive chemicals such as sulfides, acidic substances, and dissolved gases, which will corrode the inside of the pipes.
[0003] Traditional methods for addressing pipeline corrosion involve applying anti-corrosion coatings to the inside and outside of metal pipes. However, controlling the coating thickness during application is difficult. Improper techniques or uneven application can lead to uneven coating formation, which in turn can cause localized corrosion spots. Furthermore, traditional composite methods such as bonding or welding when applying anti-corrosion coatings to metal pipes often result in weak interfacial bonding, insufficient adhesion, and low production efficiency. These problems become even more pronounced when protecting the interior of metal pipes.
[0004] Therefore, in view of the problems existing in the prior art, it is necessary to provide a new corrosion-resistant pipe material with good corrosion resistance, a tight bond between the corrosion-resistant coating and the pipe material, a long service life, and a simple manufacturing process. Summary of the Invention
[0005] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a corrosion-resistant film, a pipe, a method for preparing the same, and its application, in order to solve the problems in the prior art.
[0006] To achieve the above and other related objectives, the present invention is obtained through the following technical solution.
[0007] The first aspect of this invention provides a corrosion-resistant film, wherein the raw material components of the corrosion-resistant film contain at least a modified LCP, the raw material components of which include p-hydroxybenzoic acid (p-HBA), 6-hydroxy-2-naphthoic acid (HNA), and methyl 3,4-dihydroxythiophene dicarboxylate (DHTD), wherein the molar ratio of p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and methyl 3,4-dihydroxythiophene dicarboxylate is 60-80:5-40:0.5-3. For example, it can be 60-75:20-40:0.5-3, or 62.5-75:22-37:0.5-3.
[0008] Specifically, the structural formulas of p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and methyl 3,4-dihydroxythiophene dicarboxylate are shown in Formula I, Formula II, and Formula III, respectively:
[0009]
[0010] Preferably, the number-average molecular weight of the modified LCP is 2.5w to 5w.
[0011] Preferably, the water absorption rate of the corrosion-resistant film is less than or equal to 0.5‰. For example, it can be 0.4‰ to 0.45‰, 0.1‰, 0.2‰, 0.3‰, 0.4‰, or 0.45‰.
[0012] Preferably, the tensile strength of the corrosion-resistant film is 110–140 MPa. For example, the tensile strength can be 125–133 MPa, 110–133 MPa, or 125–140 MPa.
[0013] Preferably, the elongation at break of the corrosion-resistant film is 3-5.5%. For example, the elongation at break can be 4.5-5.2%, 3-5.2%, or 4.5-5.5%.
[0014] The second aspect of this invention provides a method for preparing a corrosion-resistant thin film, the specific steps of which are:
[0015] A modified LCP is provided, and the modified LCP is granulated and then cast into a film at high temperature to obtain the corrosion-resistant film.
[0016] The modified LCP is prepared by mixing p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and methyl 3,4-dihydroxythiophene dicarboxylate in a certain proportion, and then acetylifying it with acetic anhydride under the condition of a catalyst. After the acetylation reaction is completed, the modified LCP is obtained by melt polymerization and solid-phase polymerization.
[0017] Preferably, the acetylation reaction is carried out at a temperature of 130–150°C. For example, the temperature can be 130–145°C, 130–140°C, or 140–150°C.
[0018] Preferably, the acetylation reaction takes 1 to 3 hours. For example, the time can be 1 to 2 hours or 2 to 3 hours.
[0019] Preferably, the acetylation reaction is carried out in an inert gas environment. More preferably, the inert gas includes nitrogen.
[0020] Preferably, the catalyst is one or more of potassium acetate, sodium acetate, magnesium acetate, zinc acetate, and calcium acetate.
[0021] Preferably, the catalyst content is 0.01 wt% to 0.05 wt% based on the total mass of the modified LCP feedstock. For example, it can be 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%, or 0.05 wt%.
[0022] Preferably, the molar ratio of acetic anhydride to the total components of the modified LCP feedstock is 1.01 to 1.10:1. For example, it can be 1.02 to 1.08:1, 1.02 to 1.05:1, or 1.05 to 1.08:1.
[0023] Preferably, the melt polymerization reaction includes a first-stage reaction and a second-stage reaction; the temperature of the first-stage reaction is 210–240°C; and the temperature of the second-stage reaction is 260–320°C. For example, the temperature of the first-stage reaction can be 210–230°C, 210–220°C, or 220–230°C; and the temperature of the second-stage reaction can be 260–300°C, 260–280°C, or 280–300°C.
[0024] Preferably, the reaction time of the second stage is 1 to 3 hours. For example, it can be 1 to 2 hours or 2 to 3 hours.
[0025] Preferably, acetic acid and acetic anhydride byproducts are discharged through reflux during the melt polymerization reaction.
[0026] Preferably, the second stage reaction also includes vacuuming; after the second stage reaction continues until no liquid flows out of the condenser, a vacuum is drawn with a vacuum degree of 0.01–1 kPa and a vacuuming time of 1–2 hours. For example, the vacuum degree can be 0.01–0.1 kPa or 0.1–1 kPa.
[0027] Preferably, the melt polymerization reaction is carried out in an inert gas environment. More preferably, the inert gas includes nitrogen.
[0028] Preferably, the solid-phase polymerization reaction temperature is (T) m -35)℃~(T m -25)℃, T m The melting temperature of the modified LCP is denoted as ; the solid-state polymerization reaction time is 6–12 h. For example, the solid-state polymerization reaction temperature can be 235–255℃, 245–255℃, 250–255℃, or 245–250℃; and the solid-state polymerization reaction time can be 6–8 h or 8–12 h.
[0029] Preferably, the modified LCP has a melting temperature of 270–280°C.
[0030] Preferably, the high-temperature casting temperature is 300–340°C. For example, the temperature can be 310–340°C, 310–320°C, or 300–320°C.
[0031] A third aspect of the present invention provides a corrosion-resistant pipe, wherein the inner wall of the pipe is completely coated with the corrosion-resistant film as described above.
[0032] Preferably, the pipe is one or more of stainless steel pipe, titanium alloy pipe and aluminum alloy pipe.
[0033] Preferably, the thickness of the corrosion-resistant film is 30–80 μm. For example, it can be 50–60 μm, 50–55 μm, or 55–60 μm.
[0034] The fourth aspect of the present invention provides a method for preparing the corrosion-resistant pipe as described above, comprising providing a pipe, pre-treating the inner surface of the pipe, providing the corrosion-resistant film as described above, and completely and tightly adhering the corrosion-resistant film to the inner surface of the pipe; performing high-temperature lamination and cooling to obtain the corrosion-resistant pipe.
[0035] Preferably, the pretreatment includes one or more of the following: sandblasting, grinding, cleaning, and pickling.
[0036] Preferably, the cleaning process includes ultrasonic cleaning using one or more of anhydrous ethanol or deionized water.
[0037] Preferably, the pickling treatment is performed using one or more of hydrochloric acid, sulfuric acid, dilute nitric acid, or hydrofluoric acid.
[0038] Preferably, during pickling, the concentration of acid used is 2-7%, the temperature is 40-60°C, and the pickling time is 5-10 minutes.
[0039] Preferably, the high-temperature composite temperature is 270–300°C. Alternatively, it can be 270–280°C. Or, it can be 280–300°C.
[0040] Preferably, during high-temperature lamination, a vacuum needs to be evacuated inside the tube to maintain a vacuum level of 50–100 kPa. For example, it can be 50–80 kPa or 80–100 kPa.
[0041] Preferably, the tube is kept sealed during vacuuming.
[0042] More preferably, detachable end caps are provided at both ends of the pipe to ensure that the inside of the pipe is sealed.
[0043] Preferably, a medium-frequency induction heating coil is used to provide the temperature required for high-temperature composite heating. More preferably, the frequency of the medium-frequency induction heating coil is 500–2000 Hz.
[0044] The fifth aspect of the present invention provides an application of the corrosion-resistant pipe material described above as a crude oil transportation pipeline in the oil and gas industry.
[0045] The beneficial effects of this invention are:
[0046] 1. The corrosion-resistant film provided by this invention has excellent corrosion resistance and adhesion to metals. In harsh environments, it can effectively protect metal pipes from corrosion and prevent them from falling off, thus effectively extending the life of the pipes.
[0047] 2. The method for preparing corrosion-resistant pipes provided by the present invention avoids the use of coatings to coat the inner wall of the pipe. Instead, it selects to directly attach the formed film to the inner wall of the pipe and combines it with a specific medium-frequency induction heating coil heating method, thereby effectively avoiding the uneven coating caused by spraying or spin coating processes and avoiding the formation of local corrosion spots.
[0048] The preparation method is simple and easy to operate. It also ensures a tight bond between the inner wall of the pipe and the film, resulting in strong adhesion. This effectively prevents the coating from blistering or peeling off in a short period of time. Furthermore, it is low in cost and is very suitable for large-scale promotion and use.
[0049] 3. The corrosion-resistant pipe provided by this invention has excellent corrosion resistance, strong adhesion between the internal film layer and the pipe, is not easy to fall off, can transport corrosive liquids for a long time, and has a long service life. Attached Figure Description
[0050] Figure 1 The diagram shows the heating of the tube in Embodiments 4 and 5 of the present invention during the composite film process.
[0051] Figure 1 Explanation of component designations
[0052] 1. Pipes;
[0053] 2. Medium-frequency induction heating coil;
[0054] 3. End cap. Detailed Implementation
[0055] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.
[0056] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the respective manufacturers.
[0057] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or equivalent to those described, apparatus, and materials in the embodiments of this invention may be used to implement the present invention.
[0058] This application provides a corrosion-resistant film and its preparation method. The corrosion-resistant composite film introduces methyl 3,4-dihydroxythiophene dicarboxylate into the raw material components. The introduction of the planar conjugated structure in the thiophene ring enables the modified LCP copolymer to form a denser molecular arrangement. This structural property significantly enhances the corrosion resistance of the modified LCP material after film formation. At the same time, the introduction of sulfur atoms in the thiophene ring provides the possibility for strong bonding with metal pipes.
[0059] This application also provides a corrosion-resistant pipe with excellent corrosion resistance and strong film coating adhesion, and a method for preparing the same. The preparation method involves high-temperature lamination of a modified sulfur-containing LCP film (provided in this application) with a metal pipe. This not only significantly improves the corrosion resistance of the metal pipe but also enhances the adhesion between the corrosion-resistant film and the metal surface by utilizing the coordination of the lone pair electrons of sulfur in the film with the metal surface. This preparation method avoids the problem of uneven coating in existing technologies and effectively solves the problems of weak interfacial bonding, insufficient adhesion, and low production efficiency that exist in traditional lamination methods such as bonding or welding when laminating anti-corrosion films with metal pipes. Furthermore, the high-temperature lamination method used in this application is simple to operate, low in cost, and conducive to large-scale application.
[0060] Example 1
[0061] This embodiment provides a specific corrosion-resistant thin film and its preparation method. Specifically, it includes the following steps:
[0062] 1) Preparation of modified LCP
[0063] 1-1) Acetylation reaction
[0064] 0.68 mol of p-hydroxybenzoic acid, 0.3 mol of 6-hydroxy-2-naphthoic acid, and 0.02 mol of methyl 3,4-dihydroxythiophene dicarboxylate were mixed and poured into a reaction vessel. 1.05 mol of acetic anhydride and 3.1 g of magnesium acetate catalyst were added. After evacuating the reaction vessel, nitrogen gas was introduced to protect the reactants under nitrogen protection. The mixture was then heated to 145 °C and refluxed for 2 hours to carry out the acetylation reaction.
[0065] 1-2) Melt polymerization reaction
[0066] After the acetylation reaction is completed, the temperature of the reactor is raised to 210°C, and the condensation system is turned on to carry out the first stage reaction under a nitrogen atmosphere for 1 hour. The byproducts acetic acid and acetic anhydride are separated through the condensation system. The temperature of the reactor is then raised to 260°C, and the second stage reaction is carried out under a nitrogen atmosphere for 3 hours. After no liquid flows out of the condensation system, a vacuum is drawn to a vacuum degree of 0.1 kPa and maintained for 1 hour to complete the melt polymerization.
[0067] 1-3) Solid-state polymerization reaction
[0068] After melt polymerization, the product is transferred to a solid-state polymerization apparatus, heated to 255°C, and solid-state polymerization is carried out under a nitrogen atmosphere for 8 hours to obtain the modified LCP.
[0069] 2) Preparation of corrosion-resistant thin films
[0070] The modified LCP obtained in step 1) is granulated and then cast into a film at 310°C to obtain the corrosion-resistant film with a thickness of 50 μm.
[0071] Example 2
[0072] This embodiment provides a specific corrosion-resistant thin film and its preparation method. Specifically, it includes the following steps:
[0073] 1) Preparation of modified LCP
[0074] 1-1) Acetylation reaction
[0075] 0.75 mol of p-hydroxybenzoic acid, 0.22 mol of 6-hydroxy-2-naphthoic acid, and 0.03 mol of methyl 3,4-dihydroxythiophene dicarboxylate were mixed and poured into a reaction vessel. 1.02 mol of acetic anhydride and 3.04 g of magnesium acetate catalyst were added. The reaction vessel was then evacuated and nitrogen gas was introduced to protect the reactants under nitrogen protection. The mixture was then heated to 140 °C and refluxed for 2 hours to carry out the acetylation reaction.
[0076] 1-2) Melt polymerization reaction
[0077] After the acetylation reaction is completed, the temperature of the reactor is raised to 230°C, and the condensation system is turned on to carry out the first stage reaction under a nitrogen atmosphere for 1 hour. The byproducts acetic acid and acetic anhydride are separated through the condensation system. The temperature of the reactor is then raised to 280°C, and the second stage reaction is carried out under a nitrogen atmosphere for 3 hours. After no liquid flows out of the condensation system, a vacuum is drawn to a vacuum degree of 0.1 kPa and maintained for 1 hour to complete the melt polymerization.
[0078] 1-3) Solid-state polymerization reaction
[0079] After melt polymerization, the product is transferred to a solid-state polymerization apparatus, heated to 250°C, and solid-state polymerization is carried out under a nitrogen atmosphere for 8 hours to obtain the modified LCP.
[0080] 2) Preparation of corrosion-resistant thin films
[0081] The modified LCP obtained in step 1) was granulated and then cast into a film at 320°C to obtain the corrosion-resistant film with a thickness of 60 μm.
[0082] Example 3
[0083] This embodiment provides a specific corrosion-resistant thin film and its preparation method. Specifically, it includes the following steps:
[0084] 1) Preparation of modified LCP
[0085] 1-1) Acetylation reaction
[0086] 0.625 mol of p-hydroxybenzoic acid, 0.37 mol of 6-hydroxy-2-naphthoic acid, and 0.005 mol of methyl 3,4-dihydroxythiophene dicarboxylate were mixed and poured into a reaction vessel. 1.08 mol of acetic anhydride and 4.7 g of magnesium acetate catalyst were added. After evacuating the reaction vessel, nitrogen gas was introduced to protect the reactants under nitrogen protection. The mixture was then heated to 130 °C and refluxed for 3 hours to carry out the acetylation reaction.
[0087] 1-2) Melt polymerization reaction
[0088] After the acetylation reaction is completed, the temperature of the reactor is raised to 220°C, and the condensation system is turned on to carry out the first stage reaction under a nitrogen atmosphere for 1 hour. The byproducts acetic acid and acetic anhydride are separated through the condensation system. The temperature of the reactor is then raised to 300°C, and the second stage reaction is carried out under a nitrogen atmosphere for 2 hours. After no liquid flows out of the condensation system, a vacuum is drawn to a vacuum degree of 0.1 kPa and maintained for 1 hour to complete the melt polymerization.
[0089] 1-3) Solid-state polymerization reaction
[0090] After melt polymerization, the product is transferred to a solid-state polymerization apparatus, heated to 245°C, and solid-state polymerization is carried out for 12 hours under a nitrogen atmosphere to obtain the modified LCP.
[0091] 2) Preparation of corrosion-resistant thin films
[0092] The modified LCP obtained in step 1) was granulated and then cast into a film at 320°C to obtain the corrosion-resistant film with a thickness of 55 μm.
[0093] Comparative Example 1
[0094] This comparative example provides a specific thin film and its preparation method. Specifically, it includes the following steps:
[0095] 1) Preparation of LCP in the prior art
[0096] 1-1) Acetylation reaction
[0097] The raw materials were replaced with 0.68 mol of p-hydroxybenzoic acid and 0.3 mol of 6-hydroxy-2-naphthoic acid, and methyl 3,4-dihydroxythiophene dicarboxylate was not added. The ratio of acetic anhydride and catalyst and other reaction conditions were the same as in Example 1.
[0098] 1-2) Melt polymerization reaction
[0099] Same as in Example 1.
[0100] 1-3) Solid-state polymerization reaction
[0101] As in Example 1, LCP was obtained.
[0102] 2) Preparation of corrosion-resistant composite films
[0103] After granulating the LCP obtained in step 1), the film was cast at 310°C to obtain a film with a thickness of 50 μm.
[0104] Comparative Example 2
[0105] This comparative example provides a specific thin film and its preparation method. Specifically, it includes the following steps:
[0106] 1) Preparation of LCP in the prior art
[0107] 1-1) Acetylation reaction
[0108] The raw materials were replaced with 0.68 mol of p-hydroxybenzoic acid and 0.3 mol of 6-hydroxy-2-naphthoic acid, 0.003 mol of methyl 3,4-dihydroxythiophene dicarboxylate, and the ratio of acetic anhydride and catalyst and other reaction conditions were the same as in Example 1.
[0109] 1-2) Melt polymerization reaction
[0110] Same as in Example 1.
[0111] 1-3) Solid-state polymerization reaction
[0112] As in Example 1, LCP was obtained.
[0113] 2) Preparation of corrosion-resistant composite films
[0114] After granulating the LCP obtained in step 1), the film was cast at 310°C to obtain a film with a thickness of 50 μm.
[0115] Comparative Example 3
[0116] This comparative example provides a specific thin film and its preparation method. Specifically, it includes the following steps:
[0117] 1) Preparation of modified LCP
[0118] 1-1) Acetylation reaction
[0119] The raw materials were replaced with 0.68 mol of p-hydroxybenzoic acid, 0.3 mol of 6-hydroxy-2-naphthoic acid and 0.05 mol of methyl 3,4-dihydroxythiophene dicarboxylate, and the ratio of acetic anhydride and catalyst and other reaction conditions were the same as in Example 1.
[0120] 1-2) Melt polymerization reaction
[0121] Same as in Example 1.
[0122] 1-3) Solid-state polymerization reaction
[0123] Same as in Example 1.
[0124] 2) Preparation of corrosion-resistant thin films
[0125] After granulating the modified LCP obtained in step 1), a large number of fine wrinkles appeared on the surface of the LCP particles, which seriously affected the surface smoothness of the product and did not meet the film formation conditions.
[0126] Comparative Example 4
[0127] This comparative example provides a specific thin film and its preparation method. Specifically, it includes the following steps:
[0128] 1) Preparation of modified LCP
[0129] 1-1) Acetylation reaction
[0130] The raw materials were replaced with 0.68 mol of p-hydroxybenzoic acid, 0.3 mol of 6-hydroxy-2-naphthoic acid and 0.1 mol of methyl 3,4-dihydroxythiophene dicarboxylate, and the ratio of acetic anhydride and catalyst and other reaction conditions were the same as in Example 1.
[0131] 1-2) Melt polymerization reaction
[0132] Same as in Example 1.
[0133] 1-3) Solid-state polymerization reaction
[0134] Same as in Example 1.
[0135] 2) Preparation of corrosion-resistant thin films
[0136] After granulating the modified LCP obtained in step 1), a film was cast at 310°C. It was found that the polymer in step 1) exhibited crosslinking and agglomeration, failing to meet the film-forming conditions and thus preventing film formation. This may be due to the addition of excessive amounts of methyl 3,4-dihydroxythiophene dicarboxylate.
[0137]
[0138] This comparative example provides a specific thin film and its preparation method. Specifically, it includes the following steps:
[0139] 1) Preparation of modified LCP
[0140] 1-1) Acetylation reaction
[0141] Same as in Example 1.
[0142] 1-2) Melt polymerization reaction
[0143] Except for the temperature being raised to 330°C during the second stage reaction, the remaining steps are the same as in Example 1.
[0144] 1-3) Solid-state polymerization reaction
[0145] Same as in Example 1.
[0146] 2) Preparation of corrosion-resistant thin films
[0147] After granulating the modified LCP obtained in step 1), it was cast into a film at 310°C. It was found that the polymer melt strength in step 1) was low, which made it impossible to form a film.
[0148] This may be because excessively high reaction temperatures during melt polymerization lead to excessive degradation of the polymer, resulting in a decrease in molecular weight and severely affecting the melt strength of the polymer, thus preventing film formation.
[0149] The applicant conducted performance tests on the films prepared in Examples 1-3 and Comparative Examples 1-4, including tensile strength test, elongation at break test, water absorption test, and salt spray test.
[0150] The specific testing method is as follows:
[0151] The tensile strength test method shall be in accordance with GB / T 1040.3-2006.
[0152] The test method for elongation at break shall be in accordance with GB / T 1040.3-2006.
[0153] The test method for water absorption rate shall be in accordance with GB / T 1034-2008.
[0154] The salt spray test method is in accordance with GB / T 10125-2021, which uses the acetic acid salt spray test (AASS): 5% sodium chloride acid solution of glacial acetic acid is added and atomized for testing. The test is conducted by circulating spraying until corrosion occurs on the test material. The time in Table 1 below is the time when corrosion occurs in the salt spray test.
[0155] The specific results are shown in Table 1 below.
[0156] Table 1
[0157]
[0158]
[0159] As shown in Table 1, the films in Examples 1-3 showed no corrosion after at least 1500 hours of acetic acid salt spray testing; while the films in Comparative Examples 1 and 2 showed spot-like or cloud-like discoloration and localized blistering after 1000 hours and 1200 hours respectively, indicating corrosion. This demonstrates that the films in Examples 1-3 have good corrosion resistance. Table 1 also shows that the films in Examples 1-3 have a tensile strength of 125-133 MPa, an elongation at break of 4.5%-5.2%, and a water absorption rate of 0.4-0.45‰, indicating good mechanical properties and low water absorption.
[0160] As shown in Example 1 and Comparative Example 1, compared with the thin film in Comparative Example 1, the LCP films modified with methyl 3,4-dihydroxythiophene dicarboxylate in Examples 1-3 significantly improved the corrosion resistance of the films, and no corrosion was observed after at least 1500 hours. This indicates that the addition of methyl 3,4-dihydroxythiophene dicarboxylate can enhance the corrosion resistance of the films; and the tensile strength and elongation at break of the films are improved to a certain extent.
[0161] As shown in Example 1 and Comparative Example 2, compared with the thin film in Comparative Example 2, the LCP films modified with a specific amount of methyl 3,4-dihydroxythiophene dicarboxylate in Examples 1-3 significantly improved the corrosion resistance of the films, showing no corrosion even after at least 1500 hours. This indicates that the content of methyl 3,4-dihydroxythiophene dicarboxylate is a crucial parameter; only within the specific range described in this application can the effect of at least 1500 hours without corrosion be achieved. If the content is too low, such good corrosion resistance cannot be achieved.
[0162] In summary, the corrosion-resistant film provided by this invention has good mechanical properties, excellent flexibility and mechanical stability. At the same time, the corrosion-resistant film provided by this invention has low water absorption, indicating that it has good stability in complex application environments and excellent corrosion resistance.
[0163] Example 4
[0164] This embodiment provides a specific corrosion-resistant pipe and its preparation method. Specifically, it includes the following steps:
[0165] 1) Pre-treatment of pipes
[0166] 1-1) Immerse the aluminum alloy pipe completely in anhydrous ethanol, ultrasonically clean for 10 minutes, then clean with deionized water until the inner surface of the aluminum alloy pipe is clean and free of oil and other impurities, and then dry.
[0167] 1-2) Immerse the aluminum alloy tube obtained in 1-1) completely in hydrochloric acid (concentration of 5%, temperature of 50℃) for 5 minutes, then rinse with deionized water until the aluminum alloy tube is neutral and dry.
[0168] 2) Composite corrosion-resistant film
[0169] The corrosion-resistant composite film prepared in Example 1 is completely and tightly bonded to the inner surface of the pretreated aluminum alloy tube, and a movable medium-frequency induction heating coil (frequency 500-2000Hz) is wrapped around the outer surface of the aluminum alloy tube and heated to 280°C. The medium-frequency induction heating coil is moved so that the entire tube is in an environment of 280°C.
[0170] Simultaneously, a detachable end cap is used to seal the pipe, ensuring that the inside of the pipe is sealed. A vacuum pump is connected to a section of the detachable end cap to evacuate the inside of the pipe until the vacuum level reaches 80 kPa. After maintaining the temperature and pressure for 30 minutes, the pipe is naturally cooled to obtain the corrosion-resistant pipe.
[0171] Example 5
[0172] This embodiment provides a specific corrosion-resistant pipe and its preparation method. Specifically, it includes the following steps:
[0173] 1) Pre-treatment of pipes
[0174] 1-1) Same as Example 4.
[0175] 1-2) No pickling treatment is performed.
[0176] 2) Composite corrosion-resistant film
[0177] Similar to Example 4, the corrosion-resistant pipe material was obtained.
[0178] Comparative Example 5
[0179] This comparative example provides a specific corrosion-resistant pipe material and its preparation method. The specific steps include:
[0180] 1) Pre-treatment of pipes
[0181] Completely identical to Example 4
[0182] 2) Composite corrosion-resistant film
[0183] The corrosion-resistant film used in Example 4 was replaced with the corrosion-resistant film prepared in Comparative Example 1, and the rest was the same as in Example 4.
[0184] Comparative Example 6
[0185] This comparative example provides a specific corrosion-resistant pipe material and its preparation method. The specific steps include:
[0186] 1) Pre-treatment of pipes
[0187] Completely identical to Example 4
[0188] 2) Composite corrosion-resistant film
[0189] The corrosion-resistant film used in Example 4 was replaced with the corrosion-resistant film prepared in Comparative Example 2, and the rest was the same as in Example 4.
[0190] The applicant also conducted performance tests on the pipes prepared in Examples 4-5 and Comparative Examples 5 and 6, including salt spray tests and adhesion tests.
[0191] The specific testing method is as follows:
[0192] The salt spray test method is in accordance with GB / T 10125-2021, which uses the acetic acid salt spray test (AASS): 5% sodium chloride acid solution of glacial acetic acid is added and atomized for testing. The test is conducted by circulating spraying until corrosion occurs on the test material. The time in Table 2 below is the time when corrosion occurs in the salt spray test.
[0193] The adhesion test method shall be in accordance with GB / T 5210-2006.
[0194] The specific results are shown in Table 2 below.
[0195] Table 2
[0196]
[0197] When the same salt spray test was conducted using only aluminum alloy pipes, slight white rust or pitting was found to appear on the aluminum alloy pipes after 72 hours.
[0198] As can be seen from Examples 4-5 in Table 2, the corrosion-resistant pipe provided by the invention has excellent corrosion resistance. During the acetic acid salt spray test, it can maintain its corrosion resistance for at least 1500 hours without any corrosion. Moreover, the film has strong adhesion to the pipe surface and can achieve a pull-out strength of 6.4-7.2.
[0199] As can be seen from Example 4 and Comparative Example 5 in Table 2, the pipe in Comparative Example 5 showed localized bubbles and localized detachment of the film after 500 hours. This indicates that using the LCP film modified with methyl 3,4-dihydroxythiophene dicarboxylate as described in this application is a very important technical means. If the unmodified LCP film in the prior art is used, the film has weak adhesion to the pipe surface and is easy to detach, which leads to poor corrosion resistance of the pipe.
[0200] As shown in Table 2, Examples 4 and 6, the pipe in Comparative Example 6 exhibited localized bubbles and peeling of the film after 800 hours. This indicates that using the LCP film modified with methyl 3,4-dihydroxythiophene dicarboxylate as described in this application is a crucial technical means. Furthermore, the amount of methyl 3,4-dihydroxythiophene dicarboxylate added is very specific. Only within the range provided in this application (the molar ratio of p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and methyl 3,4-dihydroxythiophene dicarboxylate is 60-80:5-40:0.5-3) can the stronger adhesion to metal achieved in this application be obtained, thereby further achieving the technical effect of maintaining non-corrosion for at least 1500 hours in an acetic acid salt spray test.
[0201] In summary, the thin film coating in the corrosion-resistant pipe provided by this invention has strong bonding ability with the metal pipe, good film adhesion, and excellent corrosion resistance.
[0202] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A corrosion-resistant film, characterized in that, The raw material components of the corrosion-resistant film contain at least modified LCP, wherein the raw material components of the modified LCP include p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and dimethyl 3,4-dihydroxythiophene-2,5-dicarboxylate, and the molar ratio of p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and dimethyl 3,4-dihydroxythiophene-2,5-dicarboxylate is 60~80:20~40:0.5~3; When subjected to an acetic acid salt spray test with a 5% sodium chloride acidic solution containing glacial acetic acid, the corrosion-resistant film showed no corrosion for at least 1500 hours; The specific steps for preparing the corrosion-resistant film are as follows: providing modified LCP, granulating the modified LCP and casting it into a film at high temperature to obtain the corrosion-resistant film; The modified LCP is prepared by mixing p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and dimethyl 3,4-dihydroxythiophene-2,5-dicarboxylate in a certain proportion, and then acetylated with acetic anhydride under the condition of a catalyst. After the acetylation reaction is completed, the modified LCP is obtained by melt polymerization and solid-phase polymerization. The melt polymerization reaction includes a first-stage reaction and a second-stage reaction; the temperature of the first-stage reaction is 210~240℃; the temperature of the second-stage reaction is 260~320℃. The solid-phase polymerization reaction temperature is (T) m -35)℃~(T m -25)℃, T m The melting temperature of the modified LCP is denoted as . The temperature for high-temperature casting is 300~340℃.
2. The corrosion-resistant film according to claim 1, characterized in that, The number-average molecular weight of the modified LCP is 2.5w to 5w; And / or, the water absorption rate of the corrosion-resistant film is less than or equal to 0.5‰; And / or, the tensile strength of the corrosion-resistant film is 110~140MPa; And / or, the elongation at break of the corrosion-resistant film is 3 to 5.5%.
3. A method for preparing a corrosion-resistant thin film as described in any one of claims 1 to 2, characterized in that, The specific steps are as follows: providing modified LCP, granulating the modified LCP and casting it into a film at high temperature to obtain the corrosion-resistant film; The modified LCP is prepared by mixing p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and dimethyl 3,4-dihydroxythiophene-2,5-dicarboxylate in a certain proportion, and then acetylated with acetic anhydride under the condition of a catalyst. After the acetylation reaction is completed, the modified LCP is obtained by melt polymerization and solid-phase polymerization. The molar ratio of p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and dimethyl 3,4-dihydroxythiophene-2,5-dicarboxylate is 60~80:20~40:0.5~3; The melt polymerization reaction includes a first-stage reaction and a second-stage reaction; the temperature of the first-stage reaction is 210~240℃; the temperature of the second-stage reaction is 260~320℃. The solid-phase polymerization reaction temperature is (T) m -35)℃~(T m -25)℃, T m The melting temperature of the modified LCP is denoted as .
4. The preparation method according to claim 3, characterized in that, The temperature for high-temperature casting film formation is 300~340℃; And / or, the temperature of the acetylation reaction is 130~150°C; And / or, the acetylation reaction is carried out in an inert gas environment; And / or, the catalyst is one or more of potassium acetate, sodium acetate, magnesium acetate, zinc acetate, and calcium acetate; And / or, during melt polymerization, acetic acid and acetic anhydride byproducts are removed by reflux. And / or, the melt polymerization reaction is carried out in an inert gas environment; And / or, the melting temperature of the modified LCP is 270~280℃.
5. The preparation method according to claim 3, characterized in that, Based on the total mass of the modified LCP feedstock, the catalyst content is 0.01 wt% to 0.05 wt%. And / or, the molar ratio of the acetic anhydride to the total components of the modified LCP feedstock is acetic anhydride: the sum of the molar numbers of the total components of the modified LCP feedstock = 1.01~1.10:1; And / or, the second stage reaction also includes evacuation; after the second stage reaction continues until no liquid flows out of the condenser, evacuation is performed with a vacuum degree of 0.01 ~ 1 kPa.
6. A corrosion-resistant pipe, characterized in that, The inner wall of the pipe is completely coated with a corrosion-resistant film as described in any one of claims 1 to 2.
7. The corrosion-resistant pipe according to claim 6, characterized in that, The pipe material is one or more of stainless steel pipe, titanium alloy pipe and aluminum alloy pipe; And / or, the thickness of the corrosion-resistant film is 30~80μm.
8. A method for preparing a corrosion-resistant pipe as described in any one of claims 6-7, characterized in that, A pipe is provided, and the inner surface of the pipe is pretreated; a corrosion-resistant film as described in any one of claims 1 to 2 is provided, and the corrosion-resistant film is completely and tightly adhered to the inner surface of the pipe; after high-temperature lamination, the pipe is cooled to obtain the corrosion-resistant pipe. The temperature for high-temperature composite is 270~300℃; During high-temperature lamination, it is also necessary to evacuate the tube to maintain a vacuum level of 50~100kPa; a medium-frequency induction heating coil is used to provide the temperature required for high-temperature lamination.
9. The preparation method according to claim 8, characterized in that, The pretreatment includes one or more of the following: sandblasting, grinding, cleaning, and pickling.
10. The application of a corrosion-resistant pipe as described in any one of claims 6 to 7 in the oil and gas industry as a crude oil transportation pipeline.
Citation Information
Patent Citations
Method for preparing liquid crystal polymer film
CN110862523A
Wear-resistant and corrosion-resistant polypropylene steel-plastic composite pipe and preparation method thereof
CN116178839A
Liquid crystal polymer, fiber and preparation method thereof, and conductive fiber
CN117510814A
